Does Employee Engagement Influence Innovative Work Behavior? A Study among Selected Food and Beverages Companies: A Study among Selected Food and Beverages Companies - Abdullah, Nor Hazana; Alias, Muhammad Haziq (Research in Management of Technology and Business, 2021)
Innovative work behaviour is one of the important factors in addressing emerging issues of sustaining competitive advantage. Innovative work behaviour consists of multistage processes of idea creation, promotion, and implementation. Employee engagement is seen as critical antecedent of innovative behavior as it motivates employees to find new ways to improve their works. As there are limited studies that identify the influence of employee engagement on innovative work behaviour, this study is to identify the relationship between employee engagement and innovative work behaviour among employees working in selected food and beverages companies. A total of 400 employees participated whist being chosen via convenient sampling technique. Well-established questionnaires by De Jong and Den Hartog (2007) and Macey (2008) were used to measure employee engagement respectively. The data obtained was analyzed descriptively and using correlation analysis via IBM Statistical Packages for Social Sciences (SPSS). Consistent with previous studies, level of innovative work behaviour in Malaysia is not high. Employee engagement has significant influence on innovative work behaviour. This study strengthened the notion on the importance of employee engagement for organizational improvement and innovativeness.